ANALISIS PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI RIAU - Handayani, Rahmita; Kadir, Hainim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study analyzes the development of Government Expenditure on Education and Health Sectors in Riau Province at period 2003-2012 and its effect to the Human Development Index (HDI). The analytical method used was descriptive quantitative by using Multiple Linear Regression Analysis, with secondary data published by BPS and other related organizations. The result shown the Government Expenditure on education and health sectors simultaneously affect the HDI. Government expenditure on education sector of Riau Province has a positive effect but not significant to HDI in the Riau Province. Government expenditure education sector in the whole district of Riau province has a positive and significant effect to HDI in the Riau Province. Government expenditure on health sector of Riau province has a positive and significant effect to HDI in the Riau Province. Government expenditure on health sector in the whole district of Riau province has a negative effect and insignificant to HDI in the Riau Province.Keywords : Human Development Index (HDI), Goverment Expenditure, Education and Health.